2010
DOI: 10.1128/jb.00196-10
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the WaaL O-Antigen Ligase Prevents Surface Activation of the Flagellar Gene Cascade in Proteus mirabilis

Abstract: Proteus mirabilis is a Gram-negative bacterium that undergoes a physical and biochemical change from a vegetative swimmer cell (a typical Gram-negative rod) to an elongated swarmer cell when grown on a solid surface. In this study, we report that a transposon insertion in the waaL gene, encoding O-antigen ligase, blocked swarming motility on solid surfaces but had little effect on swimming motility in soft agar. The waaL mutant was unable to differentiate into a swarmer cell. Differentiation was also prevented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 55 publications
1
55
0
Order By: Relevance
“…The mechanism by which FliL transmits a signal to regulate gene expression has not been defined (3). More recently, we proposed a role for the O antigen in sensing surfaces (35). We hypothesized that O antigen was needed to sense solid surfaces and to relay this signal to the cell through the Rcs phosphorelay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which FliL transmits a signal to regulate gene expression has not been defined (3). More recently, we proposed a role for the O antigen in sensing surfaces (35). We hypothesized that O antigen was needed to sense solid surfaces and to relay this signal to the cell through the Rcs phosphorelay.…”
mentioning
confidence: 99%
“…Our previous study indicated a role for O antigen in surface sensing and the Rcs phosphorelay in transmitting a surface contact signal to transcriptional regulation (35). Mutations in the waaL gene (PMI3163, formerly rfaL), encoding O-antigen ligase, and wzz (PMI2183, formerly cld), encoding a chain-length determinant for O antigen, result in the failure to derepress the class I flagellar activator FlhDC on solid surfaces.…”
mentioning
confidence: 99%
“…The swarming behavior involves a complex repeating cycle of differentiation between two cell types, the vegetative (swimmer) and swarmer cells (Janda and Abbott, 2005). The swimmer cells dominate in liquid and change into swarmer cells with longer cell length and more flagella after 3-4 h when they are placed on solid surfaces (Morgenstein et al, 2010). The flagellar rotation is inhibited during this conversion, and an extracellular signal is required to control this multicellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…RfaL (WaaL) is the lipopolysaccharide O-antigen ligase. In P. mirabilis, the deletion of rfaL causes reduced differentiation into swarmer cells primarily due to its repression of the flhDC operon (Morgenstein et al, 2010). In P. aeruginosa, the RfaL protein is a membrane protein with 11 potential transmembrane segments (Abeyrathne and Lam, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation